Vampire diaries : The Return : Midnight / [book 7] - Smith, L. J., 1965- (Lisa Jane) (Hodder Children's Books, 2011)
Elena returns from the Dark Dimension, having freed her vampire boyfriend Stefan Salvatore from imprisonment... but not without consequence. His salvation will demand a high price. Whilst still reeling from this latest shock, they are forced to confront the demons that have taken over Fell´s Church. Elena must make a decision that will cost her dear: Damon or Stefan...?